Memotivasi Mahasiswa Melakukan Penginjilan Anak melalui Pendidikan Agama Kristen - Jovan Octo Tamelab; Kristyana Kristyana (DIDAKTIKOS: Jurnal Pendidikan Agama Kristen Duta Harapan, 2021)
Every person who has faith in Jesus Christ is responsible for evangelizing. This is according to what is written in Matthew 28:19 and Mark 16:15. No exception for Christian Religious Education teachers who also have the responsibility of guiding and encouraging every student to experience an encounter with Jesus Christ. Thus, Stipak students as prospective Christian Religious Education teachers should have an understanding that evangelism is not only during college but a lifelong responsibility. This study focuses on the effectiveness of Christian Religious Education learning obtained by students in motivating evangelism to children. The research methodology used is qualitative research methods. While the data were obtained through observation, interview, and documentation techniques on the object of research, namely Stipak students who took Christian Religious Education Learning courses. From the research that has been done, it is found that students are motivated to do evangelism. The environment where students do activities is the driving force in evangelizing. These environments are family, campus / Stipak, Transformation, and church. With the existence of Christian Child Education learning students not only understand evangelism to children but also understand the importance of caring for children through the proper teaching of Jesus Christ to them. AbstrakSetiap orang beriman pada Yesus Kristus bertanggung jawab untuk melakukan penginjilan. Hal ini sesuai dengan yang tertulis dalam Matius 28:19 dan Markus 16:15. Maka tujuan penelitian ini untuk mengetahui bahwa pembelajaran Pendidikan Agama Kristen Anak yang diperoleh di Stipak dapat memotivasi mahasiswa untuk melakukan penginjilan anak. Metode penelitian yang dipergunakan adalah penelitian kualitatif dengan teknik observasi, wawancara dan dokumentasi pada obyek penelitian yaitu mahasiswa STIPAK yang mengikuti mata kuliah Pembelajaran Pendidikan Agama Kristen. Kesimpulan yang diperoleh dari penelitian ini adalah mahasiswa setelah mengikuti pembelajaran Pendidikan Agama Kristen Anak termotivasi untuk melakukan penginjilan pada anak-anak.